Hybrid structure electrode based on metal NANO wire and metal mesh and fabricating method thereof

KR103031551B1Active Publication Date: 2026-10-13KYUNGPOOK NAT UNIV IND ACADEMIC COOP FOUND
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
KR1020240165828
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2026-10-13
Estimated Expiration
2044-11-20

Smart Images

  • Figure 112024127555690-PAT00003_ABST
    Figure 112024127555690-PAT00003_ABST
Patent Text Reader

Abstract

The present invention relates to a hybrid structure electrode based on metal nanowires and a metal mesh and a method for manufacturing the same. A hybrid structure electrode according to one embodiment of the present invention comprises a metal mesh electrode formed in a network form using a crack template and a plurality of metal nanowires formed by mutual welding by heat after being spin-coated on the metal mesh electrode. The metal mesh electrode moves electrons based on the network form and transmits light through the empty spaces of the network form. The plurality of metal nanowires form additional movement paths for the moving electrons to reduce sheet resistance, and the reduced sheet resistance is maintained even if the density decreases according to the speed of the spin coating. A transparent electrode performance index can be determined based on the transmittance of light and the sheet resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a hybrid structure electrode based on metal nanowires and metal mesh and a method for manufacturing the same. More specifically, it relates to a technology for improving transparent electrode efficiency by forming an additional conduction pathway through a hybrid structure electrode created by spin-coating metal nanowires (NWs) onto a metal mesh electrode fabricated using a crack template. Background Technology

[0002] With the advent of the 21st-century ubiquitous era, the need for electronic devices is increasing due to rapidly developing information and display technologies.

[0003] Currently, communication and electronic devices are becoming increasingly smaller and lighter due to the rapid development of science and technology, and devices with various functions are required.

[0004] Indium Tin Oxide (ITO) is currently the most commonly used transparent electrode material.

[0005] ITO exhibits excellent electrical and optical properties when deposited at temperatures above 250 degrees. However, indium has poor flexibility, making it difficult to use in flexible devices, and it is scarce and has high processing costs.

[0006] Additionally, the ITO thin film has the disadvantage of reduced performance due to device degradation caused by the diffusion of oxygen atoms into the metal layer during the manufacturing process.

[0007] Silver nanowires, carbon nanotubes (CNT), graphene, conducting polymers, and metal meshes are being studied as next-generation materials that can be used as transparent electrodes.

[0008] A transparent electrode refers to a material that transmits light in the visible light region (400 nm to 800 nm) while also being electrically conductive.

[0009] Conductivity is required to process electrical signals, and transmittance is required to utilize light in the device.

[0010] To be used as a transparent electrode material, it must have a transmittance of 80% or more in the visible light region and 10 -3 Resistivity of 10 or less / cm and surface resistance 3 It must have excellent conductivity of / sq or less.

[0011] Metals exhibit high electrical conductivity due to the movement of existing free electrons, but they have a narrow energy band gap that absorbs light and displays opaque colors.

[0012] Currently, transparent electrode devices primarily refer to devices fabricated as n-type, and in such cases, the panel itself, such as PDP, LCD, or OLED, can be viewed as the device.

[0013] In addition, due to the high charge concentration, the device can be utilized as an electrode.

[0014] Transparent electrodes, which influence the characteristics of various optoelectronic devices, are essential components that determine light transmission, absorption, voltage application, and current injection and extraction.

[0015] Transparent electrode devices refer to transparent electro-optical devices of n-type or p-type transparent conductive materials that utilize semiconductor properties. They transmit light in the ultraviolet region and exhibit high reflectivity in the infrared region.

[0016] In addition, there must be a sufficient number of carriers, which are the medium for carrying electric charge, and high electrical characteristics are required because they have low resistance and can move easily.

[0017] Recently, metal meshes are being studied as transparent electrodes requiring high electrical conductivity.

[0018] A metal mesh is a transparent electrode having various shapes of patterns using metal materials such as silver and copper, which have excellent electrical conductivity, on a transparent film.

[0019] Various studies are being conducted on methods for making metal mesh transparent electrodes, such as methods that involve depositing a metal thin film, forming a pattern by photolithography, and then etching it, processes that involve coating silver nano ink and sintering it with a laser to remove the unsintered parts with an organic solvent, or processes that use screen printing.

[0020] However, these processes have the disadvantage of resulting in limitations in transparent electrode performance or reduced productivity.

[0021] Research on various alternative materials and structures is continuing to replace the currently most commonly used ITO transparent electrode devices while compensating for the aforementioned drawbacks. Prior art literature

[0022] Korean Registered Patent No. 10-2500535, "Hybrid Transparent Conductive Electrode" Korean Registered Patent No. 10-2461794, "Silver Nanowire Mesh Electrode and Method for Manufacturing the Same" Korean Registered Patent No. 10-2628299, "Method for Manufacturing a Transparent Conductive Network Using a Master Mold"

[0023] Research on Characteristic Enhancement of Ag-based Nano-hybrid Transparent Electrodes and Artificial Intelligence-based Analysis Method (February 2023) The problem to be solved

[0024] The present invention aims to improve the efficiency of transparent electrodes by forming additional conduction pathways through a hybrid structured electrode created by spin-coating metal nanowires (NWs) onto a metal mesh electrode fabricated using a crack template.

[0025] The present invention aims to provide a hybrid structural electrode that significantly reduces sheet resistance while maintaining maximum transmittance by verifying transmittance and sheet resistance according to the spin coating rate for coating metal nanowires on a metal mesh electrode and the spin coating rate for forming the metal mesh electrode.

[0026] The present invention aims to provide a hybrid structured electrode in which the density of metal nanowires on a metal mesh electrode is determined to reduce sheet resistance while maintaining transmittance, thereby increasing the effect on the conducting pathway. means of solving the problem

[0027] A hybrid structure electrode according to one embodiment of the present invention comprises a metal mesh electrode formed in a network form using a crack template and a plurality of metal nanowires formed by mutual welding by heat after spin coating on the metal mesh electrode, wherein the metal mesh electrode moves electrons based on the network form and transmits light through the empty spaces of the network form, and the plurality of metal nanowires form an additional movement path for the moving electrons to reduce sheet resistance, wherein the reduced sheet resistance is maintained even if the density decreases according to the speed of spin coating, and a transparent electrode performance index can be determined based on the transmittance of light and the sheet resistance.

[0028] The metal mesh electrode is formed by coating a metal thin film on a crack template formed by spin-coating a colloidal silica solution according to a preset speed, and as the crack width of the crack template decreases and the density increases inversely proportional to the increase in the speed of the spin-coating, the width of the network decreases and the density increases, thereby increasing the transmittance of light and sheet resistance.

[0029] The density of the plurality of metal nanowires is reduced in proportion to the spin coating speed at which a metal solution based on a conductive metal is spin-coated, and the sheet resistance can be reduced based on the mutual welding formation.

[0030] The spin coating speed of the crack template can be determined at 2000 rpm to 6000 rpm, and the spin coating speed of the plurality of nanowires can be determined at 1000 rpm to 6000 rpm.

[0031] The above transparent electrode performance index is determined based on the sheet resistance relative to the transmittance and can be increased with increasing spin coating speed for the crack template and the plurality of nanowires.

[0032] The spacing between the networks of the metal mesh electrodes can be formed to be equal to or wider than the length of any one of the plurality of metal nanowires.

[0033] Even if the width of the metal mesh electrode exceeds the length of any one of the plurality of metal nanowires, the reduced sheet resistance can be maintained based on the conductive path connection between the plurality of metal nanowires.

[0034] A method for manufacturing a hybrid structure electrode according to an embodiment of the present invention comprises the steps of: forming a crack template using a silica solution; forming a metal mesh electrode in a network form using the crack template; and forming a plurality of metal nanowires by spin-coating a metal solution based on a conductive metal onto the metal mesh electrode and then welding them together by heat. The metal mesh electrode moves electrons based on the network form and transmits light through the empty spaces of the network form, and the plurality of metal nanowires form additional movement paths for the moving electrons to reduce sheet resistance, wherein the reduced sheet resistance is maintained even if the density decreases according to the speed of the spin coating, and a transparent electrode performance index can be determined based on the transmittance of light and the sheet resistance. Effects of the invention

[0035] The present invention can improve the efficiency of a transparent electrode by forming an additional conduction pathway through a hybrid structure electrode created by spin-coating metal nanowires (NWs) onto a metal mesh electrode fabricated using a crack template.

[0036] The present invention can provide a hybrid structure electrode that significantly reduces sheet resistance while maintaining maximum transmittance by verifying transmittance and sheet resistance according to the spin coating rate for coating metal nanowires on a metal mesh electrode and the spin coating rate for forming a metal mesh electrode.

[0037] The present invention can provide a hybrid structure electrode in which the density of metal nanowires on a metal mesh electrode is determined to reduce sheet resistance while maintaining transmittance, thereby increasing the effect on the conducting pathway. Brief explanation of the drawing

[0038] FIG. 1 is a drawing illustrating a method for manufacturing a hybrid structure electrode according to an embodiment of the present invention. FIG. 2 is a drawing illustrating a hybrid structure electrode according to an embodiment of the present invention. FIGS. 3a to 3c are drawings illustrating the characteristics of a metal mesh electrode included in a hybrid structure electrode according to an embodiment of the present invention. FIGS. 4a to 4c are drawings illustrating the transmittance and sheet resistance according to the spin coating speed of a hybrid structure electrode according to an embodiment of the present invention. FIGS. 5a to 5c are drawings illustrating the transmittance and sheet resistance according to the welding of metal nanowires in a hybrid structure electrode according to an embodiment of the present invention. Figure 6 is a diagram illustrating the transparent electrode performance index (Figure of Merit, FoM) according to the spin coating speed of a hybrid structure electrode according to an embodiment of the present invention. Figure 7 is a diagram illustrating the Figure of Merit (FoM) according to the density of metal nanowires in a transparent electrode of a hybrid structure electrode according to an embodiment of the present invention. FIG. 8 is a diagram illustrating an image related to the density of metal nanowires in a hybrid structure electrode according to an embodiment of the present invention. Specific details for implementing the invention

[0039] Hereinafter, various embodiments of this document are described with reference to the attached drawings.

[0040] The embodiments and the terms used therein are not intended to limit the technology described in this document to specific embodiments and should be understood to include various modifications, equivalents, and / or substitutions of said embodiments.

[0041] In describing various embodiments below, if it is determined that a detailed description of related known functions or configurations could unnecessarily obscure the essence of the invention, such detailed description will be omitted.

[0042] Furthermore, the terms described below are defined considering their functions in various embodiments, and these may vary depending on the intentions or practices of the user or operator. Therefore, their definitions should be based on the content throughout this specification.

[0043] In relation to the description of the drawings, similar reference numerals may be used for similar components.

[0044] A singular expression may include a plural expression unless the context clearly indicates otherwise.

[0045] In this document, expressions such as "A or B" or "at least one of A and / or B" may include all possible combinations of the items listed together.

[0046] Expressions such as "first," "second," "first," or "second" may modify the corresponding components regardless of order or importance, and are used merely to distinguish one component from another without limiting the components.

[0047] Where it is stated that a certain (e.g., first) component is "(functionally or telecommunicationally) connected" or "connected" to another (e.g., second) component, said certain component may be directly connected to said other component or connected through another component (e.g., third component).

[0048] In this specification, "configured to" may be used interchangeably with, depending on the context, for example, in hardware or software, "suitable for," "capable of," "modified to," "made to," "capable of," or "designed to."

[0049] In some situations, the expression "device configured to..." may mean that the device is "able to..." together with other devices or parts.

[0050] For example, the phrase “a processor configured (or set) to perform A, B, and C” may mean a dedicated processor for performing said operations (e.g., an embedded processor), or a general-purpose processor capable of performing said operations by executing one or more software programs stored in a memory device (e.g., a CPU or an application processor).

[0051] Also, the term 'or' means an inclusive or rather an exclusive or.

[0052] That is, unless otherwise noted or is not clear from the context, the expression 'x uses a or b' means any one of the natural inclusive permutations.

[0053] Terms such as '..bu', '..gi' used below refer to a unit that processes at least one function or operation, and this may be implemented in hardware or software, or a combination of hardware and software.

[0055] FIG. 1 is a drawing illustrating a method for manufacturing a hybrid structure electrode according to an embodiment of the present invention.

[0056] FIG. 1 illustrates a method for manufacturing a hybrid structure electrode according to an embodiment of the present invention, and a procedure for manufacturing a hybrid structure electrode.

[0057] Referring to FIG. 1, in step (S101), a method for manufacturing a hybrid structure electrode according to an embodiment of the present invention spin-coates a colloidal silica solution onto a glass substrate, and then in step (S102), naturally dries the solution to form a crack template by forming a crack around the silica island.

[0058] More specifically, cleaning is performed by ultrasonic cleaning treatment for 30 minutes at each step in the order of acetone, ethanol, and deionized water, and after cleaning, a drying process is carried out using an oven to remove residual moisture remaining on the surface of the substrate.

[0059] Subsequently, to improve the adhesion between the colloidal silica solution and the substrate, OH on the surface was applied through oxygen plasma treatment. - A hydrophilic coating treatment is performed by forming a group.

[0060] The spin coating process conditions for forming a crack template can be carried out at 2000 rpm, 4000 rpm, and 6000 rpm.

[0061] To prevent unwanted cracks from occurring, a crack template can be formed by drying for 10 minutes while maintaining a relative humidity of 20% to 30% at room temperature.

[0062] When a colloidal silica solution is coated onto a glass substrate, the thin film shrinks due to capillary forces generated as the solvent evaporates.

[0063] At this time, tensile stress is applied to the thin film due to the frictional force between the substrate and the thin film, and if the critical stress that the thin film can withstand is exceeded, cracks occur, and crack templates of independent shapes can be formed.

[0064] After the drying process is complete, the final crack width and density are determined by the balance between the shrinkage force of the silica thin film and the frictional force between the film and the substrate.

[0065] Here, since the viscous friction coefficient is linear with the thin film thickness, as the spin coating speed increases—that is, as the thickness of the coated silica thin film decreases—the width of the cracks in the crack template decreases and the density increases.

[0066] The width and density of cracks act as variables that influence the characteristics of the metal mesh. In this context, it is important to form an optimal crack template given the correlation where increasing the distance between cracks leads to higher transmittance of the metal mesh transparent electrode but also increases sheet resistance.

[0067] As the spin coating speed of the colloidal silica solution increases, the crack width tends to decrease and the crack density tends to increase.

[0068] Colloidal silica solutions were fabricated by forming crack templates at spin coating speeds of 2000, 4000, and 6000 rpm, respectively, depositing a conductive metal to a thickness of approximately 150 nm, and then removing the crack templates through a lift-off process. In metal mesh transparent electrodes fabricated with crack templates under the same conditions, the light transmittance remains almost unchanged even when the thickness of the metal is varied, and the sheet resistance decreases as the silver deposition thickness increases.

[0069] However, if the metal deposition thickness exceeds 1 / 3 of the thickness of the silica thin film, the lift-off process is not properly performed and the metal mesh structure is not formed.

[0070] In such cases, the metal that should be present during the lift-off process of the crack template is removed along with it, so a metal mesh structure cannot be formed, and thus it fails to function as a transparent electrode.

[0071] In addition, when preparing a crack template with a colloidal silica solution, if the thickness of the silica film being coated is too thin, it is not possible to build up the elastic energy required for crack formation.

[0072] In step (S103), the method for manufacturing a hybrid structure electrode according to an embodiment of the present invention subsequently coats a metal thin film through a sputtering process, and then in step (S104), the method for manufacturing a hybrid structure electrode according to an embodiment of the present invention fabricates a metal mesh electrode composed of a plurality of metal mesh grids through lift-off.

[0073] A metal thin film is deposited on a 2-inch metal target by applying frequency power to the formed crack template through RF magnetron sputtering.

[0074] To perform the lift-off process, a metal mesh transparent electrode can be fabricated after removing the crack template by ultrasonically treating it in deionized water for 10 minutes.

[0075] In step (S105), a method for manufacturing a hybrid structure electrode according to an embodiment of the present invention spin-coates a metal solution based on a conductive metal onto a metal mesh electrode to form a plurality of metal nanowires, and applies heat to the formed metal nanowires to weld them.

[0076] That is, the method for manufacturing a hybrid structure electrode according to one embodiment of the present invention fabricates a hybrid structure electrode by coating metal nanowires onto a metal mesh electrode through a spin coating process.

[0077] In addition, to reduce the contact resistance between the metal nanowire and the metal mesh electrode, the metal nanowire and the metal mesh electrode are welded by applying heat of about 200 degrees in a thermal stirrer.

[0078] The transmittance of the network of metal mesh electrodes is related to the surface coverage of silver nanowires, and as the spin coating speed increases, the surface coverage of the metal nanowires decreases and the transmittance increases.

[0079] A method for manufacturing a hybrid structure electrode according to one embodiment of the present invention improves the performance of a transparent electrode by forming a plurality of metal nanowires between metal mesh electrodes to form additional electrical paths, thereby reducing sheet resistance while maintaining transmittance.

[0080] Accordingly, the present invention can improve the efficiency of a transparent electrode by forming an additional conduction pathway through a hybrid structure electrode created by spin-coating metal nanowires (NWs) onto a metal mesh electrode fabricated using a crack template.

[0082] FIG. 2 is a drawing illustrating a hybrid structure electrode according to an embodiment of the present invention.

[0083] FIG. 2 illustrates the structure and characteristics of a hybrid structure electrode according to an embodiment of the present invention.

[0084] Referring to FIG. 2, a hybrid structure electrode (200) according to one embodiment of the present invention includes a metal mesh electrode (201) and a metal nanowire (202).

[0085] The metal mesh electrode (201) is formed in a network shape using a crack template.

[0086] Multiple metal nanowires (202) are formed by spin coating on a metal mesh electrode (201) and then welding each other by heat.

[0087] The metal mesh electrode (201) moves electrons based on the network shape and transmits light through the empty spaces of the network shape.

[0088] Multiple metal nanowires (202) can form additional paths for moving electrons to reduce sheet resistance.

[0089] Additionally, the plurality of metal nanowires (202) can be determined such that the reduced sheet resistance is maintained even if the density decreases according to the spin coating speed, and the transparent electrode performance index is increased based on the light transmittance and sheet resistance.

[0090] As the density of the metal nanowires (202) decreases, the performance of the transparent electrode related to the transparent electrode performance index improves.

[0091] When the mesh spacing is different but the density of the metal nanowires (202) is the same, it shows a similar performance index.

[0092] Regardless of the density of the metal nanowires (202), the sheet resistance value of the hybrid electrode can be maintained similarly.

[0093] In a hybrid structure electrode (200) according to one embodiment of the present invention, even if the density of the metal nanowires (202) decreases, the sheet resistance reduction effect is maintained through additional movement paths between the metal nanowires (202) and with the metal mesh electrode.

[0094] Even if the density of the multiple metal nanowires (202) increases, the influence of mutual contact resistance is negligible, so it does not affect the increase in sheet resistance, and the sheet resistance is reduced by securing a conduction path.

[0095] The metal mesh electrode (201) is formed by coating a metal thin film onto a crack template formed as a colloidal silica solution is spin-coated according to a preset speed.

[0096] Additionally, as the crack width of the crack template decreases and the density increases inversely proportional to the increase in the speed of spin coating, the density of the metal mesh electrode (201) decreases and the light transmittance and sheet resistance may increase.

[0097] The density of the multiple metal nanowires (202) decreases in proportion to the spin coating speed at which a metal solution based on a conductive metal is spin-coated, and the sheet resistance can be reduced based on the formation of mutual welding.

[0098] Here, multiple metal nanowires (202) are welded to other metal nanowires and also welded to the metal mesh of the metal mesh electrode.

[0099] The crack template determines the spin coating speed at 2000 rpm to 6000 rpm.

[0100] The spin coating speed of the plurality of nanowires is determined at 1000 rpm to 6000 rpm.

[0101] The transparent electrode performance index is determined based on the sheet resistance relative to transmittance and can be increased with increasing spin coating speed for the crack template and multiple nanowires.

[0102] Even if the width of the metal mesh electrode (201) according to one embodiment of the present invention exceeds the length of the metal nanowire (202), the effect of reducing sheet resistance can be maintained through the connection of the conductive paths between the metal nanowires (202). The spacing between the networks of the metal mesh electrode (201) can be formed to be equal to or wider than the length of any one of the plurality of metal nanowires (202).

[0103] The spacing between networks of the metal mesh electrodes (201) can be formed to be 20㎛ to 35㎛.

[0104] The thickness of any one of the plurality of metal nanowires (202) can be formed to be 30 nm to 1000 nm and the length to be 25 μm to 45 μm.

[0105] Accordingly, the present invention can improve the efficiency of transparent electrodes by forming additional conduction pathways through a hybrid structure electrode created by spin-coating metal nanowires (NWs) onto a metal mesh electrode fabricated using a crack template.

[0107] FIGS. 3a to 3c are drawings illustrating the characteristics of a metal mesh electrode included in a hybrid structure electrode according to an embodiment of the present invention.

[0108] Referring to FIG. 3a, the relationship between width, electrical conductivity, and optical transmittance can be compared using a metal mesh electrode (300), a metal mesh electrode (301), and a metal mesh electrode (302).

[0109] When the width of a mesh-shaped electrode, such as a metal mesh electrode (300), a metal mesh electrode (301), and a metal mesh electrode (302), increases, the cross-sectional area of ​​the mesh also increases, thereby improving conductivity, but the transmittance decreases as the area through which light can pass decreases.

[0110] Referring to FIG. 3b, the relationship between density, electrical conductivity, and optical transmittance can be compared using metal mesh electrode (310), metal mesh electrode (311), and metal mesh electrode (312).

[0111] When the density of mesh-shaped electrodes such as metal mesh electrode (310), metal mesh electrode (311) and metal mesh electrode (312) decreases, conductivity decreases, but transmittance increases as the area through which light can pass increases.

[0112] In other words, an increase in width and a decrease in density in metal mesh electrodes similarly affect conductivity and light transmittance.

[0113] Referring to FIG. 3c, the metal mesh electrode (320) allows electrons to move along the network and light to pass through the gaps between them.

[0114] A hybrid structure electrode according to one embodiment of the present invention can reduce sheet resistance by forming additional electrical paths while maintaining transmittance in the visible light region, by forming a plurality of metal nanowires coated on a metal mesh electrode (320).

[0115] A hybrid structure electrode according to one embodiment of the present invention is implemented with a width and density that improves the performance of a transparent electrode by reducing sheet resistance while maintaining transmittance, by forming a coating of metal nanowires on a metal mesh electrode.

[0117] FIGS. 4a to 4c are drawings illustrating the transmittance and sheet resistance according to the spin coating speed of a hybrid structure electrode according to an embodiment of the present invention.

[0118] FIG. 4a illustrates, in an image, a metal mesh electrode formed according to a spin coating rate for forming a crack template in relation to a metal mesh electrode in a hybrid structure electrode according to an embodiment of the present invention, and a structure formed according to a spin coating rate for coating metal nanowires on the metal mesh electrode.

[0119] Referring to FIG. 4a, image (400) shows a metal mesh electrode formed using a crack template formed at a spin coating speed of 2000 rpm, image (401) shows a metal mesh electrode formed using a crack template formed at a spin coating speed of 4000 rpm, and image (402) shows a metal mesh electrode formed using a crack template formed at a spin coating speed of 6000 rpm.

[0120] Image (410) shows a case where metal nanowires are formed at a spin coating speed of 1000 rpm, and image (411) shows a case where metal nanowires are formed at a spin coating speed of 6000 rpm.

[0121] FIG. 4b shows the transmittance and sheet resistance for each of the metal mesh electrode and the metal nanowire constituting the hybrid structure electrode according to one embodiment of the present invention.

[0122] Referring to FIG. 4b, graph (420) represents transmittance and graph (421) represents sheet resistance.

[0123] In graphs (420) and (421), the metal mesh electrode marked with a triangle corresponds to image (402), the metal mesh electrode marked with a square corresponds to image (401), and the metal mesh electrode marked with a circle corresponds to image (400).

[0124] According to graphs (420) and (421), as the spin coating speed increases, it can be seen that both the transmittance and sheet resistance of the metal mesh electrode and metal nanowire increase.

[0125] FIG. 4c shows the transmittance and sheet resistance of a combined state of a metal mesh electrode and a metal nanowire constituting a hybrid structure electrode according to an embodiment of the present invention.

[0126] Referring to FIG. 4c, in graphs (430) and (431), the triangle mark corresponds to the form in which a metal nanowire is bonded to the metal mesh electrode of image (402), the square mark corresponds to the form in which a metal nanowire is bonded to the metal mesh electrode of image (401), and the circle mark corresponds to the form in which a metal nanowire is bonded to the metal mesh electrode of image (400).

[0127] According to graphs (430) and (431), as the spin coating speed increases, it can be seen that both the transmittance and sheet resistance of the metal mesh electrode and metal nanowire increase.

[0128] According to FIGS. 4a to 4c, the metal nanowires were fabricated at spin coating speeds ranging from 1000 rpm to 6000 rpm, and the metal mesh electrodes were fabricated at spin coating speeds ranging from 2000 rpm, 4000 rpm, and 6000 rpm, respectively. In the case of the hybrid electrode, the metal nanowires were fabricated by spin coating them at spin coating speeds ranging from 1000 rpm to 6000 rpm on metal mesh electrodes fabricated at spin coating speeds ranging from 2000 rpm, 4000 rpm, and 6000 rpm.

[0129] In the case of metal mesh electrodes, it can be observed that as the spin coating speed increases, the width of the network decreases and the density increases.

[0130] It can be observed that transmittance and sheet resistance increase as the spin coating speed increases.

[0131] In the case of metal nanowires, it can be observed that as the spin coating speed increases, the density of nanowires coated on the substrate decreases, and consequently, transmittance and sheet resistance increase.

[0132] In the case of the hybrid structure electrode according to one embodiment of the present invention, as the spin coating speed increases, the transmittance and sheet resistance show results identical to the trend of metal nanowires; however, in the combined form, it can be confirmed that there was almost no decrease in transmittance and the sheet resistance decreased rapidly.

[0134] FIGS. 5a to 5c are drawings illustrating the transmittance and sheet resistance according to the welding of metal nanowires in a hybrid structure electrode according to an embodiment of the present invention.

[0135] FIGS. 5A and 5B illustrate a comparison of the shape change of metal nanowires before and after welding in a hybrid structure electrode according to an embodiment of the present invention.

[0136] Referring to FIG. 5a, image (500) shows the state before heat treatment, and image (501) shows the state after heat treatment.

[0137] When comparing image (500) and image (501), it can be seen that the metal nanowires coated on the metal mesh electrode were welded as a result of heating the substrate corresponding to the area where the hybrid structure electrode was formed using a thermal stirrer after metal nanowire coating.

[0138] Referring to FIG. 5b, image (510) shows the state before heat treatment, and image (511) shows the state after heat treatment.

[0139] When comparing image (510) and image (511), it can be seen that the metal nanowires coated on the metal mesh electrode are welded as a result of heating the substrate corresponding to the area where the hybrid structure electrode is formed using a thermal stirrer after metal nanowire coating.

[0140] As shown in images (510) and (511), the larger the contact area between metal nanowires, the lower the contact resistance and the greater the conductivity.

[0141] In order to increase the contact area, a heat treatment process is required to reduce contact resistance through a heat treatment process after the coating treatment of metal nanowires.

[0142] Since the burrowing phenomenon at the joint of metal nanowires causes high surface roughness, the thickness of the stacked portion can be reduced through heat treatment.

[0143] Preferably, the metal nanowires can be heat-treated at 150 to 200 degrees after coating.

[0144] FIG. 5c shows the performance change before and after welding of metal nanowires in a hybrid structure electrode according to an embodiment of the present invention.

[0145] Referring to FIG. 5c, graph (520) shows the change in transmittance of the hybrid structure electrode after heat treatment generated according to the change in spin coating speed, and graph (521) shows the change in sheet resistance.

[0146] According to the data disclosed in graphs (520) and (521), the contact resistance between the metal nanowire and the metal mesh electrode is reduced while the transmittance is maintained and the sheet resistance is reduced.

[0148] Figure 6 is a diagram illustrating the transparent electrode performance index (Figure of Merit, FoM) according to the spin coating speed of a hybrid structure electrode according to an embodiment of the present invention.

[0149] Referring to FIG. 6, graph (600) shows the transparent electrode performance index for a hybrid structure electrode when the spin coating speed is 2000 rpm, graph (601) shows the transparent electrode performance index for a hybrid structure electrode when the spin coating speed is 4000 rpm, and graph (602) shows the transparent electrode performance index for a hybrid structure electrode when the spin coating speed is 6000 rpm.

[0150] Graphs (600), (601), and (602) compare the case where only a metal mesh electrode exists, the case where a metal nanowire is coated on a metal mesh electrode, and the hybrid structure electrode according to an embodiment of the present invention in which a metal nanowire is coated on a metal mesh electrode and then heat-treated.

[0151] A hybrid structured electrode according to one embodiment of the present invention demonstrates that the transparent electrode performance index is improved after multiple nanowire coatings and heat treatments.

[0152] In particular, the graph (602) shows that the calculated result of the transparent electrode performance index is improved by 162% from 141 to 370, which corresponds to the case where only mesh electrodes exist.

[0153] That is, the present invention can provide a hybrid structure electrode that significantly reduces sheet resistance while maintaining maximum transmittance by verifying the transmittance and sheet resistance according to the spin coating speed for coating metal nanowires on a metal mesh electrode and the spin coating speed for forming a metal mesh electrode.

[0155] Figure 7 is a diagram illustrating the Figure of Merit (FoM) according to the density of metal nanowires in a transparent electrode of a hybrid structure electrode according to an embodiment of the present invention.

[0156] Referring to FIG. 7, graph (700) represents sheet resistance, graph (701) represents transmittance, and graph (702) represents transparent electrode performance index.

[0157] In relation to sheet resistance, the total resistance (R) of the hybrid structure electrode total ) can be simplified as shown in the following mathematical formula 1.

[0159] [Mathematical Formula 1]

[0160]

[0162] In mathematical formula 1, the total resistance (R total ) metal mesh resistance (R mesh ), metal nanowire resistance resistance (R AgNW ), contact resistance between metal nanowires (R CAgNW ), contact resistance (R) between metal mesh and metal nanowires Chybrid It shows that it consists of ).

[0163] Contact resistance between metal nanowires (R CAgNW ) is related to the density of metal nanowires, and the contact resistance (R) between the metal mesh and the metal nanowires Chybrid) is related to the pitch of the metal mesh constituting the metal mesh electrode and the density of the metal nanowires.

[0164] In relation to the density of metal nanowires shown in the graph (700), the fact that the performance index changes according to the density of metal nanowires regardless of the mesh pitch indicates that the contact resistance between metal nanowires is small and that the effect as a conducting pathway is large.

[0165] The density of metal nanowires is related to the coating speed of the metal nanowires (2000 rpm, 4000 rpm, and 6000 rpm).

[0166] Graph (700) shows that compared to the case without metal nanowires (WO_AgNW), the sheet resistance decreases when metal nanowires are additionally formed and becomes even lower with subsequent thermal treatment, showing that the change in sheet resistance with respect to the change in the speed determining the width of the metal mesh electrode is not significant.

[0167] Graph (701) shows the change in transmittance for the same object as in Graph (700), allowing for quick verification of the effect of the width of the metal mesh electrode on transmittance.

[0168] Graph (702) shows that the hybrid structure electrode of the present invention increases the transparent electrode performance index as sheet resistance decreases and transmittance is maintained.

[0169] Preferably, the transparent electrode performance index of the hybrid structure electrode of the present invention is highest when the metal mesh electrode and the metal nanowire are formed at 6000 rpm.

[0170] In other words, the hybrid structure electrode shows that the performance index changes depending on the density of the metal nanowires, and since the contact resistance between the metal nanowires is not high, it demonstrates that it is highly effective as a conductive path.

[0171] In other words, the present invention can provide a hybrid structure electrode in which the density of metal nanowires on a metal mesh electrode is determined so that the sheet resistance is reduced while the transmittance is maintained, thereby increasing the effect on the conducting pathway.

[0173] FIG. 8 is a diagram illustrating an image related to the density of metal nanowires in a hybrid structure electrode according to an embodiment of the present invention.

[0174] Referring to FIG. 8, image (800) shows a hybrid structure electrode formed based on spin coating speeds (2000 rpm, 4000 rpm, and 6000 rpm) described in FIG. 7.

[0175] 2000 mesh and 2000 agNW indicate that metal mesh electrodes and metal nanowires are formed at 2000 rpm.

[0176] 4000 mesh and 4000 agNW indicate that metal mesh electrodes and metal nanowires are formed at 4000 rpm.

[0177] 6000 mesh and 6000 agNW indicate that metal mesh electrodes and metal nanowires are formed at 6000 rpm.

[0178] The image (800) shows that metal mesh electrodes and metal nanowires can be formed in various ways by combining them at different spin coating rates.

[0179] Additionally, image (800) shows that the hybrid structure electrode increases the transparent electrode performance index by lowering sheet resistance without affecting transmittance depending on the density of the metal nanowires.

[0181] Although the embodiments have been described above with reference to the limited drawings, those skilled in the art can make various modifications and variations from the description above. For example, suitable results can be achieved even if the described techniques are performed in a different order than described, and / or the components of the described system, structure, device, circuit, etc. are combined or assembled in a form different from described, or replaced or substituted by other components or equivalents.

[0182] Therefore, other implementations, other embodiments, and equivalents to the claims also fall within the scope of the claims set forth below. Explanation of the symbols

[0183] 200: Hybrid structure electrode 201: Metal mesh electrode 202: Metal nanowire

Claims

Claim 1 A metal mesh electrode formed in a network shape using a crack template; The device comprises a plurality of metal nanowires formed by mutual welding by heat after being spin-coated on the metal mesh electrode, wherein the metal mesh electrode moves electrons based on the network shape and transmits light through the empty spaces of the network shape, and the plurality of metal nanowires form additional movement paths for the moving electrons to reduce sheet resistance, and the reduced sheet resistance is maintained even if the density decreases according to the speed of the spin coating, and a transparent electrode performance index is determined based on the transmittance of light transmitted and the sheet resistance, wherein the inter-network spacing of the metal mesh electrode is formed to be equal to or greater than the length of at least one of the plurality of metal nanowires, and the plurality of metal nanowires form electron movement paths connected across the inter-network spacing to complement electron movement in the inter-network spacing, thereby configuring the device so that the sheet resistance is maintained even if the network density of the metal mesh electrode decreases, wherein the inter-network spacing of the metal mesh electrode is formed to be 20㎛ to 35㎛, and the length of at least one of the plurality of metal nanowires is formed to be 25㎛ to 45㎛, and the inter-network A hybrid structure electrode characterized by connecting networks spaced apart from each other across a gap. Claim 2 A hybrid structure electrode according to claim 1, wherein the metal mesh electrode is formed by coating a metal thin film on a crack template formed by spin-coating a colloidal silica solution according to a preset speed, and wherein the width of the crack of the crack template decreases and the density increases in inverse proportion to the increase in the speed of the spin-coating, and the width of the network decreases and the density increases, thereby increasing the transmittance of light and sheet resistance. Claim 3 A hybrid structure electrode according to claim 2, wherein the density of the plurality of metal nanowires decreases in proportion to the spin coating speed at which a metal solution based on a conductive metal is spin-coated, and the sheet resistance decreases based on the mutual welding formation. Claim 4 A hybrid structure electrode according to claim 1, characterized in that the spin coating speed of the crack template is determined at 2000 rpm to 6000 rpm, and the spin coating speed of the plurality of nanowires is determined at 1000 rpm to 6000 rpm. Claim 5 A hybrid structure electrode according to claim 4, wherein the transparent electrode performance index is determined based on the sheet resistance relative to the transmittance and increases with increasing spin coating speed for the crack template and the plurality of nanowires. Claim 6 delete Claim 7 delete Claim 8 A step of forming a crack template using a silica solution; a step of forming a metal mesh electrode in a network form using the crack template; The method comprises the step of forming a plurality of metal nanowires by spin-coating a metal solution based on a conductive metal onto the metal mesh electrode and then welding them together by heat, wherein the metal mesh electrode moves electrons based on the network shape and transmits light through the empty spaces of the network shape, and the plurality of metal nanowires form additional movement paths for the moving electrons to reduce sheet resistance, and the reduced sheet resistance is maintained even if the density decreases according to the speed of the spin coating, and a transparent electrode performance index is determined based on the transmittance of the light transmitted and the sheet resistance, wherein the spacing between networks of the metal mesh electrode is formed to be equal to or greater than the length of at least one of the plurality of metal nanowires, and the plurality of metal nanowires form electron movement paths connected across the spacing between networks to complement electron movement in the spacing between networks, thereby configuring the sheet resistance to be maintained even if the network density of the metal mesh electrode decreases, wherein the spacing between networks of the metal mesh electrode is formed to be 20㎛ to 35㎛, and the length of at least one of the plurality of metal nanowires is 25㎛ to A method for manufacturing a hybrid structure electrode characterized by being formed with 45㎛ and connecting networks spaced apart from each other across the inter-network spacing. Claim 9 A method for manufacturing a hybrid structured electrode according to claim 8, wherein the spin coating speed of the crack template is determined at 2000 rpm to 6000 rpm, and the spin coating speed of the plurality of nanowires is determined at 1000 rpm to 6000 rpm. Claim 10 A method for manufacturing a hybrid structure electrode according to claim 9, wherein the transparent electrode performance index is determined based on the sheet resistance relative to the transmittance and increases with increasing spin coating speed for the crack template and the plurality of nanowires. Claim 11 delete

Citation Information

Patent Citations

  • Hybrid transparent electrode and the fabricating method thereof

    KR1020150042369A

  • Manufacturing method of nanocomposite plated with network type metal layer through silica self crack and wearable electronics carbon fiber manufactured therefrom

    KR1020210102801A

  • Conductive transparent film and method for making same

    US20140326697A1

  • Composition, substrates and methods thereof

    US20160009928A1

  • Manufacturing Method of Multi Layer Structure Transparent Electrode

    KR1020190065012A